Transformation of Coastal Settlements Due to Tourism. (2016) - Lakshmi, S.R.; Shaji, T.L.
Abstract: Human interventions like industrialisation, urbanisation&commercialisation in ecologically vulnerable coastal areas often lead to deterioration of the environment. Tourism is a major economic activity which can bring significant transformations in the lives of people in a destination. Some of the changes can be beneficial in the form of economic growth and infrastructural developments leading to overall improvement in living standards. At the same time, it can also lead to adverse environmental impacts due to increased commercialisation, radical changes in land use, growth of crimes etc. Studies conducted in the town of Varkalarevealed that the coastal settlements are undergoing rapid transformations as a result of uncontrolled tourism activity in recent years. Unless immediate corrective measures are taken by the authorities, this will lead to socio- economic, physical and environmental degradation of the coastal region which will adversely affect the tourist inflow into the destination. This paper gives an overview about impacts of tourism development in coastal areas and the impact of tourism on the coastal environment of Papanasam beach in Varkala.